Transformações das religiosidades negras no Brasil: a contribuição da umbanda iniciática em Francisco Rivas Neto - Pontes, Guilherme de Sá (2022)
We start from the hypothesis that the so-called initiatory umbanda is a new religious experience developed from a reinterpretation of esoteric umbanda carried out by Francisco Rivas Neto, disciple of Woodrow Wilson da Matta e Silva and founder of the Faculty of Umbanda Theology (FTU). Umbanda would be a religious phenomenon of Angolan origin and that would have presented itself in multiple ways from syncretic processes. This phenomenological research on religion chose José Severino Croatto and Sidnei Nogueira as the main theoretical reference. The methodology used was the bibliographic review that included the reading, analysis and interpretation of books, periodicals and audiovisual materials. From a historical and anthropological approach, we sought to rescue the origin of Umbanda from the constitution of Afro-Brazilian religions in a complex syncretic process that evidences the secular structural racism that existed until the reinterpretation of the esoteric Umbanda that would result in the initiatory Umbanda. This method raised the discussion of four central themes that give conditions to verify the hypothesis of the dissertation: Afro-Brazilian religions, Eurocentrism, religious racism and syncretism. For the reading and analysis of the texts, we previously established some markers: conceptualization of Afro-Brazilian religions and an attempt to approach their expressions; introduction of the formative matrices of Afro-Brazilian religions; syncretism and religious racism; birth of umbanda; white umbanda; esoteric umbanda; initiation umbanda. The conclusion confirmed the hypothesis, clarifying the context in which the religious experience of initiatory umbanda emerged from the need to review anachronisms in the myths and rites of esoteric umbanda, draining from its bosom machismo, racism, LGBTphobia, religious intolerance and misogyny to present an inclusive, truly universalistic religious experience that meets the aspirations of contemporary society